2022
DOI: 10.1302/0301-620x.104b12.bjj-2022-0764.r1
|View full text |Cite
|
Sign up to set email alerts
|

How are adults who had Perthes’ disease functioning?

Abstract: Aims Perthes’ disease (PD) is a childhood hip disorder that can affect the quality of life in adulthood due to femoral head deformity and osteoarthritis. There is very little data on how PD patients function as adults, especially from the patients’ perspective. The purpose of this study was to collect treatment history, demographic details, the University of California, Los Angeles activity score (UCLA), the 36-Item Short Form survey (SF-36) score, and the Hip disability and Osteoarthritis Outcome score (HOOS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…A validity study through the International Perthes Study Group demonstrated that the Patient-reported Outcomes Measurement Information System (PROMIS), developed by the National Institutes of Health, has construct validity in measuring the HRQoL of pediatric patients with LCPD, setting the standard for future outcomes studies (49). A recent survey of more than 900 adults with a history of LCPD found that they had significantly lower physical, mental, and social health HRQoL scores (50). Future studies should incorporate HRQoLs to determine the effectiveness of LCPD treatment.…”
Section: Treatmentmentioning
confidence: 99%
“…A validity study through the International Perthes Study Group demonstrated that the Patient-reported Outcomes Measurement Information System (PROMIS), developed by the National Institutes of Health, has construct validity in measuring the HRQoL of pediatric patients with LCPD, setting the standard for future outcomes studies (49). A recent survey of more than 900 adults with a history of LCPD found that they had significantly lower physical, mental, and social health HRQoL scores (50). Future studies should incorporate HRQoLs to determine the effectiveness of LCPD treatment.…”
Section: Treatmentmentioning
confidence: 99%